Effect of compression stockings on running performance in men runners - Kemmler, W.; von Stengel, S.; Köckritz, C.; Mayhew, J.; Wassermann, A.; Zapf, J. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to determine the effect of below-knee compression stockings on running performance in men runners. Using a within-group study design, 21 moderately trained athletes (39.3 ± 10.9 years) without lower-leg abnormities were randomly assigned to perform a stepwise treadmill test up to a voluntary maximum with and without below-knee compressive stockings. The second treadmill test was completed within 10 days of recovery. Maximum running performance was determined by time under load (minutes), work (kJ), and aerobic capacity (ml/kg/min). Velocity (km/h) and time under load were assessed at different metabolic thresholds using the Dickhuth et al. lactate threshold model. Time under load (36.44 vs. 35.03 minutes, effect size [ES]: 0.40) and total work (422 vs. 399 kJ, ES: 0.30) were significantly higher with compression stockings compared with running socks. However, only slight, nonsignificant differences were observed for Vo2max (53.3 vs. 52.2 ml/kg/min, ES: 0.18). Running performance at the anaerobic (minimum lactate + 1.5 mmol/L) threshold (14.11 vs. 13.90 km/h, ES: 0.22) and aerobic (minimum lactate + 0.5 mmol/L) thresholds (13.02 vs. 12.74 km/h, ES: 0.28) was significantly higher using compression stockings. Therefore, stockings with constant compression in the area of the calf muscle significantly improved running performance at different metabolic thresholds. However, the underlying mechanism was only partially explained by a slightly higher aerobic capacity.